2019
DOI: 10.1155/2019/6852917
|View full text |Cite
|
Sign up to set email alerts
|

Presence of Circulating miR-145, miR-155, and miR-382 in Exosomes Isolated from Serum of Breast Cancer Patients and Healthy Donors

Abstract: miR-145, miR-155, and miR-382 have been proposed as noninvasive biomarkers to distinguish breast cancer patients from healthy individuals. However, it is unknown if these three miRNAs are secreted by exosomes. Thus, we hypothesized that miR-145, miR-155, and miR-382 in breast cancer patients are present in exosomes. We isolated exosomes from serum of breast cancer patients and healthy donors, then we characterized them according to their shape, size, and exosome markers by scanning electron microscopy, atomic … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
30
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 41 publications
(32 citation statements)
references
References 45 publications
0
30
0
Order By: Relevance
“…Considering all these aspects, the size distributions and concentrations of EVs that we obtained for the different samples are within the reported values in the literature. Previously concentrations of EVs in serum from cancer patients are between 10 9 – 10 11 particles/mL 88–91 .…”
Section: Discussionmentioning
confidence: 99%
“…Considering all these aspects, the size distributions and concentrations of EVs that we obtained for the different samples are within the reported values in the literature. Previously concentrations of EVs in serum from cancer patients are between 10 9 – 10 11 particles/mL 88–91 .…”
Section: Discussionmentioning
confidence: 99%
“…Because EVs can mirror the features of the origin and the state of the tumor, they have gained increasing attention as cancer biomarkers. An elevated number of EVs has been found in the peripheral blood of breast cancer patients compared with healthy controls [ 127 , 128 , 129 , 130 , 131 ]. However, the number of EVs alone is not specific enough for cancer diagnosis [ 132 ].…”
Section: Blood-based Biomarkersmentioning
confidence: 99%
“…is also changed in other diseases, mainly in breast cancer. Gonzalez-Villasana et al (2019) isolated exosomes from serum of breast cancer patients and healthy donors, and observed that a round shape of exosomes with a mean size of 119.84 nm in breast cancer patients and 115.4 nm in healthy donors. They detected miR-145, miR-155, and miR-382 in the exosomes isolated from serum of breast cancer patients and healthy donors.…”
Section: Theranostic Value Of Mir In Rectal Cancermentioning
confidence: 99%
“…They detected miR-145, miR-155, and miR-382 in the exosomes isolated from serum of breast cancer patients and healthy donors. The results show that exosomes isolated from the serum of breast cancer patients and healthy donors contains miR-145, miR-155, and miR-382 but not in a selective manner in breast cancer patients ( Gonzalez-Villasana et al, 2019 ). Spindlin 1 (SPIN1) was significantly elevated in drug-resistant breast cancer cell lines and tissues, compared with the chemosensitive ones.…”
Section: Theranostic Value Of Mir In Rectal Cancermentioning
confidence: 99%